SUBALTERNITAS PEREMPUAN BALI DALAM KUMPULAN CERPEN AKAR PULE KARYA OKA RUSMINI - , NANANG SYAIFUL ROHMAN; , Dr. Wening Udasmoro, M.Hum., DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Discussing subaltern in literature means reading and interpreting an authorâs view on the condition that is becoming the identity of the subalterns. In this research, it focuses on the position of Oka Rusmini as an author who is considered to represent a group of intellectuals who sought to speak for subaltern groups in her short stories. Subaltern groups refer to those who experience oppression. These groups are people who cannot speak up. Subaltern class is a group of non-elite marginal class (East) suppresses by cultural borders and knowledge producing colonial subjects. The act of subaltern is oppression subjected to the marginalized because of power and the desire to maintain power. This occurs between those who have interest with those who are marginalized. This study uses the theory of the subaltern proposed by Gayatri Chakravorty Spivak in her essay Can the Subaltern Speak?. This theory is used as a tool to analyze the problems arise in a collection of short stories written by Oka Rusmini entitled Akar Pule. Oka Rusmini as author, in the collection of short stories Akar Pule, wants to show women subaltern in Bali. Women subaltern in Bali occurs in various domains like women subaltern in culture, especially in the caste system, women subaltern in the institution of marriage, women subaltern due to the myth of maleness, women subaltern in facing social construction, and women subaltern by fellow women. Oka Rusmini as intellectuals in Bali, was only able to present as \"representative\" of the subaltern through her works. In Akar Pule, Oka Rusmini shows that as an intellectual, she was actually unable to make the subaltern women speak. The theme of subaltern women in Balinese society that she always put forward in her works is a way to uncover discourses that there is violence against women in Bali.